Unfinished journey : a world history - Perry, Marvin; Davis, Daniel F. (Boston : Houghton Mifflin, 1980)
A history textbook chronicling the rise of civilization 5000 years ago through the challenges and problems of the modern age.
Edition of 1974 published under title: Man's unfinished journey.
Includes index.
Bibliography: p. 745-746.
Keywords: World history; World history